2017
DOI: 10.1002/1873-3468.12690
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 cooperates with MBD4 to inhibit the expression of Glucocorticoid‐induced TNFR‐related protein in human T cells

Abstract: Glucocorticoid-induced TNFR-related protein (GITR) is constitutively expressed in T regulatory (Treg) cells and regulates their suppressive function. We identified two methylated CpG islands in the Gitr locus. Using a ChIP assay, we demonstrate that both DNMT1 and methyl-CpG-binding domain Protein 4 (MBD4) bind to the Gitr promoter. Moreover, knockdown of DNMT1 decreases the binding activity of MBD4. We observed much higher levels of both DNMT1 and MBD4 in human CD4 CD25 conventional T (Tconv) cells. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…The analysis of two CpGs: −121 bp to +125 bp and in exon 4 in the human Gitr gene, has confirmed total methylation in Tconv due to activation of DNMT1. As expected, Tconv possessed lower Gitr mRNA compared to Tregs and higher binding of DNMT1 and MBD4 to the promoter region [153]. During Tregs thymic maturation, illustrated by the decrease in CD24, it was reported that these cells underwent successive demethylation in the Gitr locus, which can be upregulated by the presence of IL-2 [14].…”
Section: Tnfrsf18 Methylationsupporting
confidence: 58%
“…The analysis of two CpGs: −121 bp to +125 bp and in exon 4 in the human Gitr gene, has confirmed total methylation in Tconv due to activation of DNMT1. As expected, Tconv possessed lower Gitr mRNA compared to Tregs and higher binding of DNMT1 and MBD4 to the promoter region [153]. During Tregs thymic maturation, illustrated by the decrease in CD24, it was reported that these cells underwent successive demethylation in the Gitr locus, which can be upregulated by the presence of IL-2 [14].…”
Section: Tnfrsf18 Methylationsupporting
confidence: 58%
“…The same study shows that the combined effect of MBD4 and DNMT1 depletion leads to 100 fold induction of the MSH4 gene, despite the fact that the MSH4 promoter was still methylated. Another study shows that MBD4 and DNMT1 bind to Gitr promotor and their overexpression significantly inhibits Gitr expression [40]. On the other hand MBD4 expression was not significantly different in DNMT1 positive neurons of psychotic patient with history of alcohol abuse [41].…”
Section: Discussionmentioning
confidence: 96%
“…However, it also contributes to the control of T reg fate memory by repressing the transcription of inflammatory genes. Hence, the expression level of DNMT1 to maintain T reg is carefully balanced; overexpression and deficiency both negatively affect T reg numbers, phenotype and functional capacities 54,55 . In line with this, DNA methylation at the Foxp3 locus by DNMT1 restricts Foxp3 expression to CD4 T cells as deletion of DNMT1 fosters the development of CD8 T reg 56 .…”
Section: Installation and Maintenance Of Epigenetic Control Over Treg...mentioning
confidence: 96%